Estimating a credit gap for non-financial corporations in Malta - Brian Micallef (Central Bank of Malta, 2015)
This paper documents two approaches that are used to estimate a credit gap, defined as the difference between actual developments in credit to non-financial corporations (NFCs) in Malta and a hypothetical path that would have been realised had the past historical relationships over the period 1995-2011 were to be maintained over the period 2012-2014. Both methods suggest that a credit gap emerged in 2012, which widened significantly in 2013 and 2014. As at 2014Q3, the credit gap is estimated between exteuro680 and exteuro830 million. In addition, the two approaches indicate that the credit gap will widen further over 2015-2016.
Keywords: E51; C5; G00; 330